Peningkatan Kualitas Pembelajaran Sejarah dengan Pelatihan Pembuatan Video Animasi Powtoon untuk Guru MGMP Sejarah SMA di Barito Kuala - Mansyur Mansyur; Rusdi Effendi; Daud Yahya; Mohamad Zaenal Arifin Anis (Universitas Galuh, 2026)
The phenomenon of low student motivation in History learning at Senior High Schools (SMA) is caused by several factors, such as the lack of creativity from teachers and the limited use of learning media. This impacts students' interest in revisiting learned material and lowers their learning outcomes. As a solution, effective learning media is needed, one of which is multimedia, which can enhance motivation and interaction in the learning process. In this case, the Powtoon animation video application is considered a tool that can facilitate the delivery of material in an engaging and interactive way. This study focuses on training History teachers in Barito Kuala Regency to create video-based learning media using Powtoon. The training aims to improve teachers' skills in creating e-learning supporting videos and making the teaching and learning process more engaging and easier for students to understand. The program involves History teachers who are part of the MGMP History group in Barito Kuala Regency, with the expectation that it will broaden their knowledge of using video-based animation media to improve the quality of History teaching in schools. The use of Powtoon in creating learning media is also expected to address challenges faced by teachers related to time limitations and access to learning resources, while supporting more effective and efficient learning